PS-BPR03-4: STAGED RESECTION OF SUSPECTED BILATERAL PHAEOCHROMOCYTOMA IN A PATIENT WITH END-STAGE KIDNEY DISEASE ON HAEMODIALYSIS. (January 2023) - Tsihlis, George; Lin, Raymond; Fischer, Eddy Ronald; Pandher, Ravind; Wong, Nikki
Abstract : Objective: Phaeochromocytoma is a rare finding in the dialysis population. The usual complexities of its management are complicated by diagnostic considerations of anuria and catecholamine variability in relation to dialysis, as well as reduced margins of error in perioperative fluid balance. To date, available case reports detailing management of phaeochromocytoma in dialysis patients have described unilateral lesions. We describe the management of a haemodialysis patient with resistant hypertension secondary to suspected bilateral phaeochromocytoma, to undergo staged surgical resection. We report on the surgical outcomes of the initial staged resection as well as the effect of dialysis timing (pre- and post-dialysis) on laboratory plasma metanephrine measurements. Design and Methods: Case Report A 73-year-old male on home haemodialysis presents with resistant hypertension. He has a background of end-stage kidney disease (ESKD) secondary to hypertensive nephrosclerosis, vascular disease, and Type 2 diabetes mellitus. CT imaging performed for back pain incidentally revealed contrast-enhancing lesions in the left and right adrenal glands, measuring 5.5 cm and 1.4 cm respectively (Figure 1A). PET-CT demonstrated FDG-avid lesions in bilateral adrenal glands with marked activity on PET Gallium Dotatate study, consistent with neuroendocrine tumours (Figure 1B). In the context of resistant hypertension, these were favoured to represent phaeochromocytomas. Plasma normetanephrine levels were consistent with this diagnosis at 6, 600pmol/L (Ref < 1, 079pmol/L). Blood pressure was not adequately controlled with the original anti-hypertensive regimen (irbesartan, lercanidipine, atenolol, and prazosin), with systolic values of 170–210mmHg, and was altered in the work-up for surgical resection of the lesions. Maximum alpha-receptor blockade was achieved with high-dose phenoxybenzamine (300 mg/day), and a beta-blocker (propranolol) and calcium-channel blocker (nifedipine) were added to attain pre-operative systolic blood pressures of 140–160mmHg with expected postural falls. Preoperative fluid status was adjusted via haemodialysis ultrafiltration, balancing the risks of intraoperative hypotension with anaesthetic considerations of potential pulmonary oedema. Results: The patient underwent laparoscopic resection with initial removal of the left adrenal lesion (Figure 1C), confirmed on histopathology to be phaeochromocytoma (Figure 1D). Blood pressures intraoperatively were maintained with minimal vasopressor support, and postoperatively with no support, consistent with expected outcomes in a staged resection of suspected bilateral phaeochromocytomas. A right adrenalectomy is planned in two months. Conclusion: This is the first reported case of suspected bilateral phaeochromocytoma in an ESKD patient on haemodialysis, and highlights the associated complexities of diagnosis and management. We demonstrate staged resection of bilateral lesions can be a safe approach in this high-risk population.